Macroeconomics, Domestic Credit and Institutional Quality on Foreign Direct Investment in ASEAN - Rafiuddin, Muhammad; Endraswati, Hikmah; Wibowo , Muhammad Ghafur (Jurnal Ilmu Ekonomi JIE, 2024)
Foreign Direct Investment (FDI) is one of the external capital flows that has many benefits for the host country in closing the savings and investment gap. The purpose of this study is to examine and explain the factors that affect the inflow of foreign capital to ASEAN countries from 2013-2022 through a fixed effect model approach. This study found that economic growth, open trade, and total domestic credit have a significant positive effect while institutional quality has a significant negative effect on FDI inflows in ASEAN countries. The findings of this study provide implications that can be taken into consideration for government agencies to make policies that are on the conditions of each country to attract investors to invest in ASEAN countries, especially in maintaining the country's economic growth rate, ease of access to global trade and finance followed by improvements in terms of bureaucratic reform of institutional quality.